2006
DOI: 10.1038/sj.ijir.3901449
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation by visual erotic stimuli in healthy middle aged males

Abstract: The objective of the present study was to identify brain centers, whose activity changes are related to erotic visual stimuli in healthy, heterosexual, middle aged males. Ten heterosexual, right-handed males with normal sexual function were entered into the present study (mean age 52 years, range 46-55). All potential subjects were screened over 1 h interview, and were encouraged to fill out questionnaires including the Brief Male Sexual Function Inventory. All subjects with a history of sexual arousal disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 20 publications
3
37
0
Order By: Relevance
“…However, physiological and behavioral differences between animals and humans make it difficult to directly apply the results to humans. Of the few Effect of SSRI on EEG of premature ejaculation patients OY Kwon et al studies in humans, most have used PET or functional magnetic resonance imaging, [17][18][19] measuring changes in cerebral blood flow or changes in oxygen concentration in blood flow to indirectly reflect neuronal activity. These methods are widely accepted, but their limitations must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, physiological and behavioral differences between animals and humans make it difficult to directly apply the results to humans. Of the few Effect of SSRI on EEG of premature ejaculation patients OY Kwon et al studies in humans, most have used PET or functional magnetic resonance imaging, [17][18][19] measuring changes in cerebral blood flow or changes in oxygen concentration in blood flow to indirectly reflect neuronal activity. These methods are widely accepted, but their limitations must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kim et al (2006) presented 10 heterosexual healthy males with film clips of relaxing scenes, sports, and sexually arousing erotic scenes. The authors found that the sexual arousal stimuli were associated with an activation of the occipitotemporal area, anterior cingulate gyrus, insula, orbitofrontal cortex, and caudate nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study of middle-aged men who did not have either ED or reduced sexual desire, the hypothalamus and thalamus were not activated in response to erotic stimuli, which may help account for the lesser physiological arousal in response to erotic visual stimuli. 37 Although spinal neurons controlling erection are activated by information from peripheral and supraspinal sources, some supraspinal structures that have a pro-erectile effect may not project directly onto spinal neurons involved in erection. These structures, including the paraventricular nucleus and the medial preoptic area of the hypothalamus, regulate erection by coordinating responses of the body during sexual or pro-sexual activity.…”
Section: Cns Pathway Of Sexual Dysfunctionmentioning
confidence: 99%